Public Management Reform and Innovation: Research, Theory, and Application - Frederickson, H. George; Johnston, Jocelyn (University of Alabama Press, 2015)
Leading scholars present the most complete, as well as the most advanced, treatment of public management reform and innovation available The subject of reform in the public sector is not new; indeed, its latest rubric, reinventing government, has become good politics. Still, as the contributors ask in this volume, is good politics necessarily good government? Given the growing desire to reinvent government, there are hard questions to be asked: Is the private sector market model suitable and effective when applied to reforming public and governmental organizations? What are the major political forces affecting reform efforts in public management? How is public management reform accomplished in a constitutional democratic government? How do the values of responsiveness, professionalism, and managerial excellence shape current public management reforms? In this volume, editors H. George Frederickson and Jocelyn M. Johnston bring together scholars with a shared interest in empirical research to confront head-on the toughest questions public managers face in their efforts to meet the demands of reform and innovation. Throughout the book, the authors consider the bureaucratic resistance that results when downsizing and reinvention are undertaken simultaneously, the dilemma public managers face when elected executives set a reform agenda that runs counter to the law, and the mistaken belief that improved management can remedy flawed policy.